Synergistic effects of para-hydroxy meta-methoxy chalcone (pHmMC)- doxorubicin treatments on T47D breast cancer cells - Retno Arianingrum; Retno Sunarminingsih; Edy Meiyanto; Sofia Mubarika (Indonesian Journal of Biotechnology, 2015)
Resistance to some cancer chemotherapeutic drugs has been identifed. One strategy to overcome that problem is by combining two or more of the drugs to get co-chemotherapeutic effects. A derivate chalcone, 3 - (4’-hydroxy-3’-methoxyphenyl)-1-phenyl-2-propene-1-on or para hydroxy meta methoxy chalcone (pHmMC), has been reported to have cytotoxic activity on some cancer cells through some pathways. The aim of this study was to investigate the effects of combinations of pHmMC and Doxorubicin (Dox) on the cytotoxicity, anti-proliferation, apoptosis, and the cell cycle of T47D (breast cancer cell-lines) in vitro. The cytotoxic and antiproliferative activity were determined by MTT (3-[4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide] assay. The combination index (CI) was used to determine the synergistic, additive or antagonistic effects of the combinations. Flowcytometry method was performed to determine the combination effects on the apoptosis and cell cycle. The results indicated that the combinations had a higher inhibitory effect on the cell growth compared to those of single treatments of pHmMC and Dox. All the doses used in the combinations were lower of the single doses at their IC50s. The results showed all the combinations gave synergistic (CI: 0.3 – 0.7) up to strong synergistic (CI: 0.1 – 0.3) effects. The synergistic effects of the combinations were due to increased apoptosis and induced cell cycle arrest in S and G2/M phases on the cancer cell lines.